Feasibility Evaluation of Probolinggo – Banyuwangi Toll Road from Economic and Financial Perspective Using Viability Gap Funding (VGF) Analysis - Fajramadhani, Adhitya Wijdan; Kartika, Anak Agung Gde (Jurnal Transportasi: Sistem, Material, dan Infrastruktur, 2023)
Roads function as connectivity between regions. Probolinggo and Banyuwangi are areas in East Java province connected by the North Coast route. Toll roads aim to expedite traffic. The construction of the Probolinggo-Banyuwangi Toll Road is planned to connect Probolinggo and Banyuwangi regency. For the planning of the Probolinggo –Banyuwangi Toll Road to be efficient and worthy of investment, it is necessary to evaluate the feasibility of the Probolinggo – Banyuwang Toll Road from economic and financial perspectives. Feasibility evaluation of the Probolinggo – Banyuwangi Toll Road used the Jasa Marga method. Furthermore, this study analyzed Vehicle Operating Costs and time value, and trip assignments were calculated to determine the number of vehicles moving from the Probolinggo – Banyuwangi national road to the planned toll road. Benefit Cost Ratio (BCR), Net Present Value, and Internal Rate of Return parameters were used to analyze the feasibility from the economic aspect so that the savings obtained by road users could be known when passing through the Probolinggo – Banyuwangi Toll Road. Meanwhile, Benefit Cost Ratio, Net Present Value, Internal Rate of Return, and Payback Period parameters were used to analyze the feasibility from the financial aspect. After analysis, it was stated that the Probolinggo – Banyuwangi Toll Road project had a degree of saturation value on the national road with project was 0.55 in 2024, while for the national road without project was 0.67. The economic feasibility analysis complied with the guidelines reviewed and stated that the project was feasible with an NPVe value of IDR Rp54.972.572.042.962, a BCRe value of 3.189, and EIRR of 6.7%. However, for the financial feasibility analysis was stated that the project was not feasible to carry out, either using interest rates as a reference or the company’s MARR as a reference. For interest rates as a reference, it was obtained NPVf of -IDR 10.074.299.894.469, BCRf of 0.599, FIRR of 3.28%, and PP exceeds the concession period of 35 years. For the company’s MARR as a reference, it was obtained NPVf of -IDR 17.233.979.248.285, BCRf of 0.31, FIRR 2.23%, and PP exceeds the concession period of 35 years. Then, the Viability Gap Funding was obtained IDR 10.074.299.894, which was allocated for land acquisition costs.